Środki budżetowe na realizację polityki interwencyjnej agencji płatniczych w Polsce w dekadzie przełomu wieków (1996-2005) - Czyżewski, Andrzej (Budgetary Expenses for Realization of Intervention Policy of Payment's Agencies in Poland on the Turn of the Centuries (1996-2005), 2005)
The purpose of the matter under discussion is the analysis of the budgetary acts in the years 1996-2005 in order to estimate the size and structure of the means destined for the realization of the intervention policy in the agri-food sector particularly for payements agencies. One makes a thorough analysis of budgetary expenses for two agencies - ARR and ARiMR. Now is it proved that expenses which are planned in yearly budgets are not able to take the edge off basic problems of agriculture and Polish rural area - incomes' inequality, low level of standards civilization, state of infrastructure. Financial condition of this sector was changed for a short time before the accession of Poland to the European Union (2003-2004). Expenses' participation of agriculture, development of rural area and agricultural markets in the light of all budgetary expenses increases substantially, which causes premises for the breakthrough agricultural policy in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 120-128